PROTOTYPE DEVICE FOR MEASURING WATER LEVEL HEIGHT WITH SOLAR PANEL AND BATTERY POWER SOURCE IN CENTRAL KALIMANTAN PEATLAND - Elvan; Fherdika Boy; Julian Prakarsa; Muhammad Firza; Fajar Sukmawan Aritama; Lola Cassiophea; Vontas Alfenny Nahan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
This research aims to develop a prototype tool for measuring water level (TMA) in the peatlands of Central Kalimantan by utilizing renewable energy from solar panels and batteries as the main environmentally friendly power source. The system is designed based on the ESP32 microcontroller integrated with a submersible transducer sensor based on the hydrostatic principle to improve measurement accuracy and stability compared to ultrasonic sensors, which tend to be affected by temperature and humidity conditions. This device is also equipped with a data logger and IoT connectivity for real-time data monitoring through the Firebase platform, enabling remote supervision without the need for direct presence in the field. The research process includes the design of wiring diagrams and PCBs, physical assembly of components, system programming, as well as testing voltage, current, and power parameters to evaluate the efficiency and performance of the device's energy system. The test results show that the prototype is capable of operating independently, with a TMA measurement accuracy of ±2.5 cm and a high correlation between electrical parameters and system performance (R² = 0.94). This tool is expected to be an effective, cost-efficient, and sustainable solution for monitoring water surface levels in remote and hard-to-reach areas.